A STUDY ON THE RELATIONSHIP BETWEEN THE QUALITY OF WORK LIFE OF P.G COLLEGES’ EMPLOYEES AND THEIR JOB SATISFACTION DURING COVID-19 IN TELANGANA STATE. - Koorella, Mr. Gnaneshwar; Dr.R.Perumal, (The journal of contemporary issues in business and government, 2022)
This article was written to inform about the job satisfaction and QWL of the faculty working in postgraduate colleges in Telangana. The QWL and Job satisfaction is a vital factor for every employee. I want to convey through this article that it is the responsibility of colleges to provide the quality of life and professional satisfaction that employees’ desire. For writing this article, a set of constructive questions was distributed and the responses were collected and analyzed. Along with them, I considered past articles and case studies. I took 160 PG College Teachers from Telangana as respondents and recorded their responses. I used a 5-point Likert scale to record responses. Since it is a study related to the survey, I used simple percentage analysis for data analysis.